2015
DOI: 10.1111/1559-8918.2015.01049
|View full text |Cite
|
Sign up to set email alerts
|

From Inspiring Change to Directing Change: How Ethnographic Praxis Can Move beyond Research

Abstract: This paper reflects on the evolving nature of ethnographic praxis in industry and argues that we must move beyond research and towards strategy in order to elevate our praxis, and to deliver real impact and value for our clients. Although this conversation is not new for the EPIC community, there has been a lack of models and examples – even in its tenth year – for how to do so. Taking a project with a medical device company that manufacturers voice prostheses for laryngectomees as a case study, we show how a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In a sense, though, the bigger challengeand one that faces any radical piece of research -is how to move from insight to impact. How to engender and sustain momentum over the period necessary to realize a bold vision is a challenge previous presentations at EPIC have emphasized (Hou & Holme 2015;Hoy & Rowley 2016). Hoy & Rowley (2016) argue that successful implementation is less a question of scale and more a question of whether the components of the network (the people and shared resources) have the capacity to deliver the strategy.…”
Section: Creating Strategic Momentummentioning
confidence: 99%
“…In a sense, though, the bigger challengeand one that faces any radical piece of research -is how to move from insight to impact. How to engender and sustain momentum over the period necessary to realize a bold vision is a challenge previous presentations at EPIC have emphasized (Hou & Holme 2015;Hoy & Rowley 2016). Hoy & Rowley (2016) argue that successful implementation is less a question of scale and more a question of whether the components of the network (the people and shared resources) have the capacity to deliver the strategy.…”
Section: Creating Strategic Momentummentioning
confidence: 99%
“…Yet we still grapple with three fundamental challenges in doing the work that defines applied ethnography: framing our research to obtain thick data when we are in the field, making sense of that data in teams and with clients, and making a convincing case with data in challenging environments, to mobilize change. (Some of these perennial challenges and the reasons behind them -such as demands to do our work faster and cheaper, and client perceptions that we only offer consumer research and not strategy, are explored in Lombardi 2009 andHou &Holmes 2015. ) In our daily work on projects across various sectors, we have observed that drawing on literary genres to guide our thinking has greatly helped us grapple with these fundamental challenges.…”
Section: Introductionmentioning
confidence: 99%
“…In each project, like in prior work in industry, it was critical to dedicate significant time while framing the study on better understanding the client organization (Hou and Holme, 2015). This meant taking an ethnographic lens to the organizations themselves: understanding the organizational culture, attending new-employee training, visiting research labs and production facilities, conducting internal interviews across functions, and joining sales meetings and internal review sessions.…”
Section: Introduction To Four Project Engagements Across the B2b Valumentioning
confidence: 99%